Community perception and participation of urban farming activities - Mohd. Hussain, Mohd. Ramzi; Yusoff, Norul Hafizah; Tukiman, Izawati; Abu Samah, Mohd Armi (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Dynamic of urban farming brings a significance which contributed by the fast growth of urban population. In some developed countries like Japan and Singapore, the approaches of urban farming inside of the buildings of residential, offices or workplaces, commercial and industrial lots at the city center were already begin to pop-up and embedded. Farming knowledge can form an effective and good intervention for city dwellers to move uplift to the better education and stand right at the higher degree of social cohesion. The aim of the paper is to investigate the community perception and later about their participation, which will support the embedment process of farming activities in urban areas. The paper employed quantitative method in eliciting the collected data. The Statistical Package Solutions for Social Science (SPSS) Version 24.0 software is used to analyses the data. The findings show that the urban dwellers have a favorable perspective concerning urban farming approach. Economical aspects in living expenses proved a great significant different in generating desires on growing food for self-consumption and saving the cost in food expenditure. The paper also indicates that beneficial practices to grow valuable urban farming activities in Malaysia as the support from each community are required to make excellent promotion for everyone to realize and concern on the importance of growing foods in fast growing urban cities especially in terms of environmental, social, economic and healthy lifestyles.